Serious fun! : work and play with Charles & Ray Eames - Hale, Christy (Holiday House, 2025)
"Twentieth-century design duo Charles and Ray Eames had serious fun experimenting and solving problems. In all that they did, they let fun lead the way; the only rules were no rules, no limits and no getting bored. Though best known today for their timelessly iconic leather lounge chairs, the Eameses were always trying something new. They made furniture in every shape they could think of, bending and layering plywood on a homemade contraption. They made short films, designed textiles and arranged museum exhibits, dabbled in architecture and photography. They even tried their hand at toy design, wanting to give kids tools to foster free thinking and exploration -- the same principles that fueled their own work." --